Economic Development, Competition Policy, and the World Trade Organization - Hoekman, Bernard; Mavroidis, Petros C. (World Bank, Washington, DC, 2014)
At the recent World Trade Organization (WTO) ministerial meeting in Doha, Qatar, WTO members called for the launch of negotiations on disciplines relating to competition based on explicit consensus on modalities to be agreed at the fifth WTO ministerial meeting in 2003. WTO discussions since 1997 have revealed little support for ambitious multilateral action. Proponents of the WTO antitrust disciplines currently propose an agreement that is limited to "core principles"-nondiscrimination, transparency, and provisions banning "hard core" cartels. The authors argue that an agreement along such lines will create compliance costs for developing countries without addressing the anticompetitive behavior of firms located in foreign jurisdictions. To be unambiguously beneficial to low-income countries, any WTO antitrust disciplines should recognize the capacity constraints that prevail in these economies, make illegal collusive business practices by firms with international operations that raise prices in developing country markets, and require competition authorities in high-income countries to take action against firms located in their jurisdictions to defend the interests of affected developing country consumers. More generally, a case is made that traditional liberalization commitments using existing WTO fora will be the most effective means of lowering prices and increasing access to an expanded variety of goods and services.